Increasing Receipt of Women's Preventive Services - Stolp, Haley (J Womens Health (Larchmt), 2015)
The receipt of clinical preventive services is important for health promotion and prevention of illness, death, and disability for women in the United States. Today, the Affordable Care Act makes a variety of evidence-based preventive services available with no out-of-pocket cost to women with certain health insurance plans. Nevertheless, available service receipt data suggest receipt of the services for all American adults remains suboptimal. This article seeks to raise awareness about the critical gaps in the delivery of preventive services to women and highlight opportunities for women, primary care providers, and public health professionals to increase receipt of clinical preventive services among women.